An Analysis of EFL Students’ Difficulties in Listening Comprehension at STKIP Muhammadiyah Bogor - Muhammad Khoerul Hadist; Hidjanah Hidjanah; Dtakiyatuddaaimah Dtakiyatuddaaimah; Lucky Dewanti (Jurnal Educatio FKIP UNMA, 2022)
The purpose of this study is to find out the difficulties or problems and the factor encounter by students in listening comprehension aimed to prepare teacher to help Student difficulties and solve the problems during teaching. This research used qualitative descriptive method. The procedure data employ the questionnaire in collecting data. 61 EFL Students of STKIP Muhammadiyah Bogor as participants. Ther resultd revealed that there were some factors affected to EFL learner in listening comprehension such as listening material, listener attitude and background knowledge, speaker and physical setting, but the most difficulites faced students in this case were lengt speech its about 60%, and unfamiliar words its about 80% in listening material variable. Meanwhile, for the listener attitude and background knowledge at the least there were two items the most difficulties faced such as catching linking word its about 54% and catching proper word its about 44%. The last and the most significant difficulties faced was the speaker and physical setting such as in unclear recorder resulting from poor CD or casset its is about 93%, and poor of recording quality and poor of equipment both of them approximate 90%.